DAMPAK PEMBANGUNAN EKONOMI, PENGELUARAN RUMAH TANGGA, DAN KETERBUKAAN PERDAGANGAN TERHADAP KONSUMSI ENERGI FINAL DI INDONESIA - Cahyono, Bambang Priyo; Hakimah, Yusro (Universitas Indo Global Mandiri Palembang, 2019)
This study investigates the impact of economic growth on three main development sectors, household final consumption expenditure, and trade openness towards the growth of final energy consumption in Indonesia using annual data for the period 1972-2016. We applied autoregressive distributed lag (ARDL) procedures which consist of stationarity test, cointegration test, as well as estimation the short-term and long-term relationships. The cointegration test revealed existence cointegrationrelationship among the variables in the model. In the short-term and long-term model, our results indicated that the growth of value-added in agriculture sector and industry sector, household final consumption expenditures, and trade openness in the short-term and long-term have a significant effect toward final energy consumption in Indonesia, while the growth of value-added in the service sector only given a short-term effect toward final energy consumption in Indonesia. Based on theseresults, it can be concluded that sustainable economic development in Indonesia needs to be accompanied by the development of new and renewable energy in order to fulfil domestic energy supply which is predicted to continue to increase rapidly in the future.Keyword : final energi consumption, economic development, household final consumption expenditure, trade openness, autoregressive distributed lag modelingJEL Classification : D1, E21, F14, O13, Q43.